(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The spread of the COVID-19 epidemic has led the World Health Organisation to declare COVID-19 as a pandemic. It has affected various sectors, especially the economic, social, educational and health sectors. This situation also affects the zakat institution when the poverty rate and those affected by health problems increase. It will certainly have a significant impact on the collection of zakat, which is declining, and the distribution of zakat is increasing. This requires zakat institutions to formulate new strategies in dealing with this adverse impact. Thus, the study is to examine the strategy of the Perlis Islamic Religious Council & Malay Customs (MAIPs) in the management of zakat to address the impact of COVID-19 in Perlis. Data were obtained through literature review and empirical data. A review of the literature related to the concept of zakat, reforms in zakat management, emergency zakat assistance and Perlis zakat institutions to understand how scholarly studies have discussed these topics. Furthermore, a virtual interview session was conducted with two MAIPs officers directly involved in zakat management in Perlis. Interview sessions were conducted to obtain holistic information on MAIPs strategies in zakat management to address the impact of COVID-19 in Perlis. Then, some themes can be generated from the interview data before it is analysed based on the content analysis method. The study results show that MAIPs received 3,500 new asnaf recipients in 2021. The increase saw a total of 18,179 asnaf under MAIPs at this time compared to 14,679 asnaf existing recipients where it involved an increase of 24%. The findings also show that MAIPs has undertaken several initiatives in balancing between distribution and collection of zakat, such as collaborating with several external agencies to improve the effectiveness of zakat distribution, enhance digital capabilities in zakat distribution and collection as well as increase zakat payment awareness campaigns led by The President of MAIPs is the Raja Muda of Perlis DYTM Tuanku Syed Faizuddin Putra Ibni Tuanku Syed Sirajuddin Jamalullail.